Validation of sensitive spectrophotometric method for determination of Salmeterol xinafoate and Fenoterol hydrobromide via o-Phenanthroline and iron complexation - Mohamed A. Hammad, Mahmoud A. Omar, Mohamed Awad (Journal of Applied Pharmaceutical Science, 2017)
A Simple, accurate and sensitive spectrophotometric method has been established and validated for the determination of two selective beta-2 agonist drugs namely; Salmeterol xinafoate and Fenoterol hydrobromide in their pure forms and pharmaceutical preparations. The proposed method is based on the ability of studied drugs to reduce iron (III) in (o-phenanthroline)-iron (III) complex to form highly stable colored tris (o-phenanthroline)-iron (II) complex that can be measured spectrophotometrically at 510 nm. Different variables affecting the reaction were studied and optimized to ensure maximum sensitivity of the method. The developed method was found to obeys Beer’s law in the concentration range of (0.7-7.0) and (1.0-8.0) µg mL-1 with quantitation limits 0.523 and 0.705 µg mL-1, for Salmeterol and Fenoterol, respectively. The suggested method was completely validated according to the ICH guidelines and successfully applied for determination of the studied drugs in their pharmaceutical preparations with high accuracy.
Keywords: Salmeterol, Fenoterol, Iron, o-phenanthroline, spectrophotometry.